Integration of pharmacogenetic data in epic genomic module drives clinical decision support alerts - Newsom, Kimberly J.; Hall, Bradley; Martinez, Katherine A.; Nelson, Scott; Starostik, Petr; Nguyen, Khoa (Frontiers in Pharmacology, 2024)
Introduction The Precision Medicine Program (PMP) at the University of Florida (UF) focuses on advancing pharmacogenomics (PGx) to improve patient care. Methods The UF PMP, in collaboration with the UF Health Pathology Laboratory (UFHPL), utilized Health Level Seven (HL7) standards to integrate PGx data into Epic’s Genomic Module to enhance the management and utilization of PGx data in clinical practice. Results A key feature of the Genomic Module is the introduction of genomic indicators—innovative tools that flag actionable genetic information directly within the electronic health record (EHR). These indicators enable the effective presentation of phenotypic information and, when leveraged with existing clinical decision support (CDS) alerts, help provide timely and informed therapeutic decisions based on genomic data. Discussion This advancement represents a significant shift in the utilization of genetic data, moving beyond traditional PDF reports to provide a comprehensive understanding of PGx data. Ultimately, this integration empowers healthcare providers with genomics-guided recommendations, enhancing precision and personalization in patient care, contributing significantly to the advancement of personalized medicine.